CoreTrustSeal Certification - much more than a certification: empowering DataRepositoriUM's processes towards FAIR data and skilled data curators - Príncipe, Pedro (2023)
Comunicação proferida no "Dataverse Community Meeting 2023", 5-7 June 2023, Braga, Portugal.